Association Between Dietary Intake and Lipid-lowering Therapy: Prospective Analysis Using a Quantile Regression Approach (OR22-03-19). (13th June 2019) - Gadowski, Adelle; Nanayakkara, Natalie; Heritier, Stephane; Magliano, Dianna; Shaw, Jonathan; Curtis, Andrea; Zoungas, Sophia; Owen, Alice
Abstract: Objectives: Lipid-lowering therapy (LLT) is ideally accompanied by dietary guidance for cardiovascular risk reduction, however current evidence suggests sub optimal dietary behaviours in those on pharmacological interventions. This study examines associations between daily intake of major food groups (vegetable, fruit, cereal, protein and dairy) and LLT use in Australian adults. Methods: Data were analysed from 5895 participants of the Australian Diabetes, Obesity and Lifestyle Study (AusDiab) aged ≥ 25 years. Medical history and dietary intake was obtained at baseline (1999–00) and follow up (2004–05). LLT use was categorised as: LLT users, commenced LLT, ceased LLT, and non-users. The association between dietary intake and LLT use was examined using quantile regression, at the 25th, 50th and 75th quantile of dietary intake. Analysis was adjusted for known risk factors. Results: A total of 446 participants remained on LLT from baseline to follow up; 565 participants commenced LLT; 71 participants ceased LLT and 4813 were non-users. Less than 1% of the cohort met recommended intakes of all food groups at baseline and follow up, with no difference by LLT status. Median daily dietary intake at follow up among LLT users was 2.2 serves of vegetables, 1.4 serves of fruit, 2.8 serves of cereal, 2.0 serves of protein and 1.4 serves of dairy. Dietary intake was similar across all LLT groups. LLT use was not significantly associated with dietary intake at the 25th, 50th and 75th quantile. Conclusions: Adjusted quantile regression analysis showed no differences in median daily intake of key food groups in LLT users, compared to non-users. The dietary behaviours observed suggest that all adults, regardless of their medication regimen, need additional education on improving their dietary intake. These findings emphasise the importance of addressing adherence to dietary guidelines, for people with chronic disease, with special focus on people requiring LLT. Funding Sources: Nil Supporting Tables, Images and/or Graphs: